Staphylococcus aureus persisters are associated with reduced clearance in a catheter-associated biofilm infection - Theis, Trenten J.; Daubert, Trevor A.; Kluthe, Kennedy E.; Brodd, Kenan L.; Nuxoll, Austin S. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Staphylococcus aureus causes a wide variety of infections, many of which are chronic or relapsing in nature. Antibiotic therapy is often ineffective against S. aureus biofilm-mediated infections. Biofilms are difficult to treat partly due to their tolerance to antibiotics, however the underlying mechanism responsible for this remains unknown. One possible explanation is the presence of persister cells—dormant-like cells that exhibit tolerance to antibiotics. Recent studies have shown a connection between a fumC (fumarase C, a gene in the tricarboxylic acid cycle) knockout strain and increased survival to antibiotics, antimicrobial peptides, and in a Drosophila melanogaster model. Objective It remained unclear whether a S. aureus high persister strain would have a survival advantage in the presence of innate and adaptive immunity. To further investigate this, a fumC knockout and wild type strains were examined in a murine catheter-associated biofilm model. Results Interestingly, mice struggled to clear both S. aureus wild type and the fumC knockout strains. We reasoned both biofilm-mediated infections predominantly consisted of persister cells. To determine the persister cell population within biofilms, expression of a persister cell marker (Pcap5A::dsRED) in a biofilm was examined. Cell sorting of biofilms challenged with antibiotics revealed cells with intermediate and high expression of cap5A had 5.9-and 4.5-fold higher percent survival compared to cells with low cap5A expression. Based on previous findings that persisters are associated with reduced membrane potential, flow cytometry analysis was used to examine the metabolic state of cells within a biofilm. We confirmed cells within biofilms had reduced membrane potential compared to both stationary phase cultures (2.5-fold) and exponential phase cultures (22.4-fold). Supporting these findings, cells within a biofilm still exhibited tolerance to antibiotic challenge following dispersal of the matrix through proteinase K. Conclusion Collectively, these data show that biofilms are largely comprised of persister cells, and this may explain why biofilm infections are often chronic and/or relapsing in clinical settings.